2021
DOI: 10.1039/d1qo00916h
|View full text |Cite
|
Sign up to set email alerts
|

Amine hydrochloride salts as bifunctional reagents for the radical aminochlorination of maleimides

Abstract: Amine hydrochloride salts have been typically used as amination reagents. Contrary to conventional use, HCl is released as waste residue. Herein, we disclose a new utilization of amine hydrochloride as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…In addition, the addition of one equivalent CuBr 2 into the reaction of 1 a and 2 a did not produce bromoaminated maleimide (eq. 5), which indicated that the present reaction mechanism was completely different from the previously found mechanism [5b,c] . In addition, when 3 a and 5 a were stirred under optimal reaction conditions, the alkylation product 4 a was obtained (eq.…”
Section: Resultscontrasting
confidence: 63%
“…In addition, the addition of one equivalent CuBr 2 into the reaction of 1 a and 2 a did not produce bromoaminated maleimide (eq. 5), which indicated that the present reaction mechanism was completely different from the previously found mechanism [5b,c] . In addition, when 3 a and 5 a were stirred under optimal reaction conditions, the alkylation product 4 a was obtained (eq.…”
Section: Resultscontrasting
confidence: 63%
“…56 To confirm whether this molecular packing motif is present in the solid, powder X-ray diffraction (PXRD) was measured. It turns out that the diffraction peaks in the calculated pattern, 57 based on the crystal structure, coincide with the measured one (Figure 4A, B). This can prove the presence of channels for the polycrystalline form, suggesting the potential use of 2 as a sorbent material.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, according to our best knowledge, we present for the first time a method for the synthesis of DDSQ amine hydrochloride salt, which has better stability than the amine derivative. Their interesting reactivity can be used in some specific functionalization methods, which are unapproachable for amine groups, i.e., aminochlorination of maleimides, 57 amide synthesis using aldehydes, 58 ring-opening polymerization, 59 , 60 Mannich reaction, 61 Chichibabin pyridine synthesis, 62 4-amino imidazole synthesis, 63 or the synthesis of pyrrolin-4-ones. 64 …”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the catalytic amount of HI promoted the unexpected radical aminochlorination of maleimides. Beyond a common solvent, the use of cheap 1,2-dihaloethane as a halogenated reagent could complement the limitation of HCl, and conventional electrophilic halogenation reagents such as NXS (X = Cl, Br) [12] enabled the previously unreachable electrondeficient alkenes twofold aminochlorination and oxidative aminobromination. The current strategy not only reduces the waste of halogen salt but also broadens the application range of 1,2-dihaloethane.…”
Section: Entrymentioning
confidence: 99%